HUBUNGAN KUALITAS PELAYANAN KARYAWAN ROOM BOY DENGAN KEPUASAN TAMU YANG MENGINAP DI HOTEL ROCKY PLAZA PADANG - Diansyah, Tisra; Chair, Ira Meirina; Pramudia, Heru (Journal of Home Economics and Tourism, 2015)
The purpose of this study are: (1) Describe the service quality of room boy employess, (2) Describe the customer satisfaction and (3) Analyze the relationship between room boy service quality employee towards customer satisfaction who stay over night Rocky Plaza Hotel Padang. The research is correlational. Research The population of this study are, all the guest who ever stayed at the Rocky Hotel Plaza Padang. A sample of 98 customers are taken incidentally. Data was collected using a questionnaire that had been tested for validity and reliability. Furthermore the data were analyzed by descriptive and correlation with the help of computer program SPSS version 16.00.The results showed that: (1) The service quality of the room boy employee positioned the very good category (96%), (2) the guest satisfaction positioned the very good category (95%) and (3) There is a positive and significant relationshipÂ between room boy employee service quality and customer satisfaction with the value of r amounted to 0,851 (0,000 sig) and interpreted that these two variables has strong relationship